New Zealand : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that economic growth in New Zealand slowed in early 2003 but rebounded in the latter part of the year. Real GDP growth declined from 4u percent in 2002 to a seasonally adjusted annualized rate of 2 3/4 percent in the first half of 2003, amid heightened international geopolitical tensions, concerns about SARS, and declines in farm output and hydroelectric generation related to a drought. The New Zealand dollar appreciated substantially during 2002 and 2003, but has depreciated somewhat since reaching a seven-year high in mid-February 2004.